2014
DOI: 10.1371/journal.pone.0100633
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Increases Mucus Synthesis in Bronchial Epithelial Cells

Abstract: Airway epithelial mucus hypersecretion and mucus plugging are prominent pathologic features of chronic inflammatory conditions of the airway (e.g. asthma and cystic fibrosis) and in most of these conditions, women have worse prognosis compared with male patients. We thus investigated the effects of estradiol on mucus expression in primary normal human bronchial epithelial cells from female donors grown at an air liquid interface (ALI). Treatment with estradiol in physiological ranges for 2 weeks caused a conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 28 publications
(34 reference statements)
1
50
0
2
Order By: Relevance
“…Surprisingly, ovarian hormones increased Alt Ext-induced mucus production even though ovarian hormones did not increase IL-13+ ILC2. Previous reports have shown that estrogen, signaling through estrogen receptor-β, increased MUC5AC expression and mucus production in cultured airway epithelial cells (Tam et al, 2014), suggesting that sex hormones may regulate mucus production through multiple pathways. Our studies did not determine the mechanisms by which ovarian hormones regulated ILC2-induced airway inflammation nor take into account other cell types, including T cells, macrophages, and dendritic cells that sex hormones are known to regulate (Fuseini and Newcomb, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, ovarian hormones increased Alt Ext-induced mucus production even though ovarian hormones did not increase IL-13+ ILC2. Previous reports have shown that estrogen, signaling through estrogen receptor-β, increased MUC5AC expression and mucus production in cultured airway epithelial cells (Tam et al, 2014), suggesting that sex hormones may regulate mucus production through multiple pathways. Our studies did not determine the mechanisms by which ovarian hormones regulated ILC2-induced airway inflammation nor take into account other cell types, including T cells, macrophages, and dendritic cells that sex hormones are known to regulate (Fuseini and Newcomb, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Administration of ethynyl oestradiol to guinea pigs significantly increased mucus cell hyperplasia compared to vehicle treated animals (79). Further, administration of estrogen or progesterone to cultured human airway or nasal epithelial cells the expression of the mucus proteins, Muc5AC and Muc5B, as well as mucus production when compared to vehicle treated cells (80, 81). Progesterone also decreased cilia beat frequency from cultured primary human airway epithelial cells, but cells that were co-administered 17b-E2 with progesterone had cilia beat frequency that was similar to vehicle treated cells (82).…”
Section: Role Of Sex Hormones In Airway Physiologymentioning
confidence: 99%
“…A recent report by Sheridan et al showed non-genomic estrogen inhibition of basal STIM1 phosphorylation followed by reduction in SOCE in airway epithelia (Sheridan et al, 2013). Estrogen also increases MUC5AC and is involved in post-translational modification (glycosylation) of mucins in human airways, this effect largely mediated by ERβ (Tam et al, 2014). Overall, these limited data suggest substantial effect of estrogens in the bronchial epithelium.…”
Section: Contribution Of Sex Steroids To Airway Structure and Funcmentioning
confidence: 99%